2019
DOI: 10.1371/journal.pone.0221828
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inulin alters the gut microbiome, enhances systemic metabolism and reduces neuroinflammation in an APOE4 mouse model

Abstract: The apolipoprotein ε4 allele ( APOE4 ) is the strongest genetic risk factor for Alzheimer’s disease (AD). APOE4 carriers develop systemic metabolic dysfunction decades before showing AD symptoms. Accumulating evidence shows that the metabolic dysfunction accelerates AD development, including exacerbated amyloid-beta (Aβ) retention, neuroinflammation and cognitive decline. Therefore, preserving metabolic function early on may be critical to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 72 publications
6
96
0
Order By: Relevance
“…Given that AD has a complex pathology and that therapies that effectively halt the disease progression are still lacking, recent studies have focused on environmental components and diet-based possible prevention strategies by using transgenic animal models (161,162). In this context, several studies have established the benefits of a healthy microbiome on slowing AD and the correlation of dysbiosis with disease progression (7, 138,163). Consistent with this notion, a study by Zhang and coworkers showed that the microbiota composition and diversity were perturbed and the level of SCFAs was reduced in AD mice, predicting alterations in more than 30 metabolic pathways, which may be associated with amyloid deposition and ultrastructural abnormalities in the APP/PS1 mouse model (25).…”
Section: Scfas and Alzheimer's Diseasementioning
confidence: 99%
“…Given that AD has a complex pathology and that therapies that effectively halt the disease progression are still lacking, recent studies have focused on environmental components and diet-based possible prevention strategies by using transgenic animal models (161,162). In this context, several studies have established the benefits of a healthy microbiome on slowing AD and the correlation of dysbiosis with disease progression (7, 138,163). Consistent with this notion, a study by Zhang and coworkers showed that the microbiota composition and diversity were perturbed and the level of SCFAs was reduced in AD mice, predicting alterations in more than 30 metabolic pathways, which may be associated with amyloid deposition and ultrastructural abnormalities in the APP/PS1 mouse model (25).…”
Section: Scfas and Alzheimer's Diseasementioning
confidence: 99%
“…Unique contributions of the gut microbiota at each site to overall host health are not yet fully clarified but are likely dependent on diet ingredients and overall health of the host [12]. The gut microbiome in combination with diet, with the subsequent translocation of microbial metabolites from the intestine to the bloodstream, is likely to play a pivotal role in influencing systemic metabolism [13][14][15]. Inulin-associated alterations in the composition of the gut microbiota are well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Prebiotics are dietary supplements used as food source by the microflora that offer a health benefit to the host regulating gut microbiota composition. Inulin, a well-studied prebiotic compound, enhanced systemic metabolism and decreased hippocampus inflammatory gene expression modulating gut microbiome composition in E4FAD mice even before the development of Ab [170]. Treatment of APP/PS1 transgenic mice with fructooligosaccharides (FOS), commonly found in fruits and vegetables, changed microbiota composition and activated the GLP-1 pathway with consequent amelioration of cognitive deficits and pathological changes.…”
Section: Preclinical Studies In Animal Modelsmentioning
confidence: 99%